2003
DOI: 10.1016/s0092-8674(02)01254-0
|View full text |Cite
|
Sign up to set email alerts
|

A Stimulatory Role for cGMP-Dependent Protein Kinase in Platelet Activation

Abstract: It is currently accepted that cGMP-dependent protein kinase (PKG) inhibits platelet activation. Here, we show that PKG plays an important stimulatory role in platelet activation. Expression of recombinant PKG in a reconstituted cell model enhanced von Willebrand factor (vWF)-induced activation of the platelet integrin alpha(IIb)beta(3). PKG knockout mice showed impaired platelet responses to vWF or low doses of thrombin and prolonged bleeding time. Human platelet aggregation induced by vWF or low-dose thrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
258
7
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(296 citation statements)
references
References 44 publications
19
258
7
6
Order By: Relevance
“…29 However, other reports have negated the presence of eNOS in platelets 30 and 1 group has even provided evidence that platelet-derived NO and its second messenger, cGMP, have a stimulatory role on platelet activation. 31 Similarly, studies on the role of platelet-derived NO in thrombosis models in vivo have given conflicting results, with data in favor of A B Figure 7. The effect of dl-nebivolol, l-nebivolol, d-nebivolol, and bisoprolol on systemic blood pressure in eNOS −/− (A) and wild type (B) mice.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, other reports have negated the presence of eNOS in platelets 30 and 1 group has even provided evidence that platelet-derived NO and its second messenger, cGMP, have a stimulatory role on platelet activation. 31 Similarly, studies on the role of platelet-derived NO in thrombosis models in vivo have given conflicting results, with data in favor of A B Figure 7. The effect of dl-nebivolol, l-nebivolol, d-nebivolol, and bisoprolol on systemic blood pressure in eNOS −/− (A) and wild type (B) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although NO, by elevating intracellular cGMP, is known to inhibit platelet activation [18], it has been recently demonstrated that the major NO synthase (NOS) isoform expressed in platelets, the endothelial NOS (eNOS), may play a stimulatory role in low dose agonist-induced platelet activation and promote an in vivo thrombotic response in an injuryinduced arterial thrombosis model [15,17]. Such stimulatory role of eNOS would be dependent on NO-mediated sGC activation and elevation of cGMP, which in turn would promote the aggregation-dependent platelet secretion of granules contents [15,17]. Additional evidence indicates that low concentrations of NO promote a discrete platelet degranulation [23].…”
mentioning
confidence: 99%
“…Additional evidence indicates that low concentrations of NO promote a discrete platelet degranulation [23]. Given these latest findings, the current concept of NO signalling needs to be revised highlighting the plausible biphasic role of NO in platelet activation; at the low concentrations, produced by platelet eNOS, NO would promote platelet secretion and aggregation, while at higher concentrations NO would inhibit platelet activation [15,17]. 1 …”
mentioning
confidence: 99%
“…Moreover, data from an in vivo study reported that the NO/cGMP pathway may inhibit the signaling cascade of thromboxane A 2 receptor through phosphorylation by cGMP-dependent protein kinase (cGK), and through collagen-induced AA release by suppressing Ca 2þ -activated phospholipase A 2 activity [27]. Changes in the activity of platelet eNOS are responsible for abnormal platelet activation: recent evidence indicates a complex biphasic interaction between NO and platelet activation and aggregation; platelet-derived NO may stimulate platelets [28] through an initial transient stimulatory response, able to promote platelet aggregation, and a subsequent inhibitory response that limits the size of thrombi. Additional evidence indicates that low NO concentrations promote a platelet degranulation; on the contrary, high NO concentrations inhibit the exocytosis of dense granules [29].…”
Section: Discussionmentioning
confidence: 99%